Large Stokes-shift bioorthogonal probes for STED, 2P-STED and multi-color STED nanoscopy. (23rd December 2020) - Török, György; Cserép, Gergely B; Telek, András; Arany, Dóra; Váradi, Melinda; Homolya, László; Kellermayer, Miklós; Kele, Péter; Németh, Krisztina
Abstract: Synthesis and multiple STED imaging applications of four, red-emitting (610–670 nm), tetrazine-functionalized fluorescent probes (CBRD = Chemical Biology Research group Dye 1–4 ) with large Stokes-shift is presented. Present studies revealed the super-resolution microscopy applicability of the probes as demonstrated through bioorthogonal labeling scheme of cytoskeletal proteins actin and keratin-19, and mitochondrial protein TOMM20. Furthermore, super-resolved images of insulin receptors in live-cell bioorthogonal labeling schemes through a genetically encoded cyclooctynylated non-canonical amino acid are also presented. The large Stokes-shifts and the wide spectral bands of the probes enabled the use of two common depletion lasers (660 nm and 775 nm). The probes were also found suitable for super-resolution microscopy in combination with two-photon excitation (2P-STED) resulting in improved spatial resolution. One of the dyes was also used together with two commercial dyes in the three-color STED imaging of intracellular structures.